Struktur Mikro pada Rubrik Pemberitaan Hukum dan Kriminal di Saluran CNN Indonesia - Dina Syafatul Kulsum; Mariam Ulfa; Junal Junal (Universitas Muhammadiyah Jember, 2025)
This research aims to explain and explore the text structure in the legal and crime reporting column on CNNIndonesia.com through Van Dijk's critical discourse analysis approach. The main focus in this research is on micro structure. Micro structure refers to the smallest elements in discourse which include details forming discourse to give a more lively impression to the reader which includes aspects such as sentence form, coherence between sentences, as well as the choice of lexicon or vocabulary. The type of research used is qualitative research. The data used for this research is in the form of digital text from the law and crime section on the CNNIndonesia.com website. Data was collected using the note-taking method and analyzed using the description method to define the elements contained in the microstructure of legal and criminal reporting. The results of the research will explore how the elements of the microstructure presented by the author can influence readers' perceptions in news discourse. Microstructure research in legal and criminal reporting sections can provide valuable insight into how digital news media, especially CNNIndonesia.com, is able to manage words and present information regarding the news issues discussed, so that it can influence readers' perceptions of the text they read. This research can open up the reader's critical thinking through word choice and the way information is presented in the text so that it influences the information the reader receives. Keywords: sentence form; coherence; lexicon